Mixture - Related Factors Influencing Setting for Ambient Curing of Fly Ash – Based Geopolymer Binders - Kwandiwe Magugu; Stephen Ekolu; Abdolhossein Naghizadeh; Henrry Quainoo (Computational Engineering and Physical Modeling)
Ambient–cured plain geopolymer binders typically exhibit unacceptably prolonged setting time values and weak development of mechanical properties. In this paper, a focussed literature review was done on setting time effects of physical – chemical factors comprising sodium hydroxide concentration, liquid – to – solids ratio, sodium silicate – to – sodium hydroxide ratio, and the influence of precursor composition. Subsequently, an experimental study was done wherein 0% to 30% ground granulated blast–furnace slag (GGBS) or ordinary Portland cement (OPC) were incorporated into fly ash – based geopolymer (FA - GPC) mixtures to compare effects of the two setting time modifiers. Paste and mortar mixtures were subjected to compressive strength, drying shrinkage, and pore – related physical properties tests.It was found that a strong correlation exists between setting time and lime content or Ca/Al ratio of the precursor. Indeed, the starting materials that had compositional values of 5% to 20% CaO and/or Ca/Al ratio of 0.5 to 1.5, were found to exhibit stable performance. Incorporation of 10% OPC gave initial /final setting time values of 65 /106 mins that met standard criteria specified in EN 197-1 (2011) and/or ASTM’s C150. It was also observed that incorporation of 10% OPC and 20% GGBS exhibited contrasting shrinkage effects, wherein the former decreased while the latter significantly increased drying shrinkage to exceed the 0.10% maximum limit stipulated in ASTM C596.